REVIEW OF ESTIMATION OF AGE FROM ERUPTION OF TEETH IN THE AGE-GROUP 6-11 YEARS - Bandyopadhyay, Soma Bandyopadhyay; Bose, TK; Paul, P (Journal of Indian Academy of Forensic Medicine, 2024)
Estimation of age is a valuable tool to assist in administration of justice in civil and criminal cases. Children with undocumented birth date  are vulnerable to violation of various child rights. Dental techniques for estimation of age are currently considered the best in assessing  true chronological age as dental development is less affected than skeletal development by malnutrition and hormonal disorders.  Estimation of age by eruption of teeth is the best choice as it is non-invasive and more economical. To study the age of eruption of  permanent teeth of children in the age-group 6-11 years of both sexes of Kolkata. To compare the findings with the time of eruption  determined from previous studies and note any variations in age of eruption of teeth in relation to sex, socio-economic status, food habits.  An observational, cross sectional, institution based, descriptive study on 144 school-going children of age group 6 years to 11 years  randomly from various schools in Kolkata was done for the eruption of permanent teeth. Number of teeth erupted was observed and noted  as per FDI chart. Data collected during the study was tabulated and verified using standard statistical tools. Out of a total 144 children  72(50%) were male children and 72(50%) were female children in the age group of 6-11 years. Eruption times of permanent teeth were  noted in various age groups. According to the present study there has been no significant change in the age of eruption of permanent teeth  over the years. The earliest tooth to erupt is the first mandibular molar. Permanent teeth erupted few months earlier in females as compared  to males. Permanent teeth appeared earlier in the lower jaw than in upper jaw except first premolar on the left side. Majority of the teeth  erupted earlier in the left quadrant as compared to the right quadrant.
Keywords: Age estimation; Tooth eruption; Child rights